Швидкість збіжності ціни європейського опціону на ринку, на якому стрибок ціни акції рівномірно розподілений на деякому інтервалі - Мішура, Ю.С.; Соловейко, О.М. (Український математичний журнал, 2008)
Рассмотрена модель рынка, на котором скачок цены акции равномерно распределен на некотором симметричном интервале, и найдена скорость сходимости справедливых цен европейских опционов с применением теоремы об асимптотических разложениях функции распределения суммы независимых одинаково распределенных случайных величин. Показано, что существует мартингальная мера на рынке в допредельной модели такая, что скорость сходимости цен европейских опционов к цене Блэка - Шоулса имеет порядок 1/n 1/2. We consider a model of market for which the jump of the stock price is uniformly distributed over a certain symmetric interval. By using the theorem on asymptotic expansions of the distribution function of the sum of independent identically distributed random variables, we determine the rate of convergence of fair prices for the European options. It is shown that, in the prelimit model, there exists a martingale measure on the market such that the rate of convergence of the prices of European options to the Black-Scholes price has an order of 1/n 1/2.